2009
DOI: 10.1038/ajh.2009.83
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Control With Bedtime Aspirin Administration in Subjects With Prehypertension

Abstract: According to the Seventh Report of the Joint National Committee, 1 prehypertension is a designation chosen to identify individuals at high risk of developing hypertension and suffering cardiovascular events. 2,3 In a recent study, Hansen et al. 4 found that progression from optimal or normal blood pressure (BP) to high-normal BP or hypertension carries nearly the same risk for cardiovascular events as sustained high-normal BP or hypertension. The Trial of Preventing Hypertension study 5 has suggested that tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 35 publications
2
41
1
Order By: Relevance
“…In fact, successful PROBE trials, such as the Hypertension Optimal Treatment (HOT) trial [25], have included a placebo arm and robust methods to preserve the masking of the treatments. Although a recent meta-analysis of PROBE trials suggests that double blinding may not be needed in trials of antihypertensive drugs based on ABPM [24], it is worth noting that investigators involved in decisions about ABPM data quality and analysis in those trials were blinded to treatment assignment and (contrary to the trials of Hermida et al [14,15,16•]) had no easy way to discover the assignment. Moreover, ABPM removes observer bias and expectation but not regression to the mean and participantrelated factors that contribute to the placebo effect [26].…”
Section: Effect Of Aspirin In Nontreated Hypertensive Individualsmentioning
confidence: 98%
“…In fact, successful PROBE trials, such as the Hypertension Optimal Treatment (HOT) trial [25], have included a placebo arm and robust methods to preserve the masking of the treatments. Although a recent meta-analysis of PROBE trials suggests that double blinding may not be needed in trials of antihypertensive drugs based on ABPM [24], it is worth noting that investigators involved in decisions about ABPM data quality and analysis in those trials were blinded to treatment assignment and (contrary to the trials of Hermida et al [14,15,16•]) had no easy way to discover the assignment. Moreover, ABPM removes observer bias and expectation but not regression to the mean and participantrelated factors that contribute to the placebo effect [26].…”
Section: Effect Of Aspirin In Nontreated Hypertensive Individualsmentioning
confidence: 98%
“…It targets the main cardiovascular risk factors during bereavement, is inexpensive, is widely available, does not require a prescription, and is feasible in other short-term interventions. Low-dose aspirin is widely used for its antiplatelet effect, has anti-inflammatory properties, and positively influences depressed mood [4], HRV [5], and blood pressure [6].To investigate aspirin as a feasible preventive intervention, acutely bereaved participants (n = 10) were recruited on average within 30 days (SD = 14.67) of the death of their spouse; nonbereaved controls (n = 12) were also recruited. We assessed hemodynamic markers (blood pressure, heart rate, HRV) and depressive symptoms (Center for Epidemiologic Studies Depression Scale; CES-D) during 2 laboratory visits.…”
mentioning
confidence: 99%
“…43 Hermida et al showed that low-dose ASA (100 mg) had a favorable effect on blood pressure of patients in a study consisting of 244 prehypertension patients. 44 Recent studies have also demonstrated that ASA induces NO release from vascular endothelium. This effect appears to be due to a direct acetylation of the endothelial NO synthase protein.…”
Section: Discussionmentioning
confidence: 99%
“…This effect appears to be due to a direct acetylation of the endothelial NO synthase protein. 44 Systemic inflammation impairs endothelium-dependent dilatation in humans and provides direct evidence that pretreatment with an anti-inflammatory dose of aspirin protects from this endothelial dysfunction. This vasculoprotective effect of aspirin does not seem to be attributable to inhibition of vascular constrictor prostanoid synthesis, because locally infused aspirin did not restore endothelial function in vaccinated subjects.…”
Section: Discussionmentioning
confidence: 99%